1998
DOI: 10.1007/s001670050068
|View full text |Cite
|
Sign up to set email alerts
|

Lateral meniscal tears and their evolution in acute injuries of the anterior cruciate ligament of the knee

Abstract: Arthroscopic diagnosis was used to determine the incidence of the most frequent injuries to the knee's internal structures associated with ACL tear as well as ones without ACL tear. The most frequent finding associated with a recent ACL tear was the LM tear (72.7%). There is a statistically significant incidence of recent LM tear in knees with a recent ACL tear compared with recently injured knees without an ACL tear (P < 0.001). A statistically significant incidence of longitudinal LM tear was found in knees … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
57
2
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 17 publications
(17 reference statements)
6
57
2
2
Order By: Relevance
“…Other studies have reported that the meniscal tears are generally the longitudinal type and localized to peripheral part of the posterior horn [6,15,20,30]. They also report that the incomplete meniscal tears were more prevalent in the lateral meniscus when compared to the medial meniscus [6,30].…”
Section: Discussionmentioning
confidence: 72%
“…Other studies have reported that the meniscal tears are generally the longitudinal type and localized to peripheral part of the posterior horn [6,15,20,30]. They also report that the incomplete meniscal tears were more prevalent in the lateral meniscus when compared to the medial meniscus [6,30].…”
Section: Discussionmentioning
confidence: 72%
“…In combined soft tissue injuries, lateral meniscal tears have been reported to significantly outnumber medial tears in conjunction with medial collateral ligament and ACL tears [29]. Following acute knee twisting injury in 66 patients, the most frequent injury in conjunction with acute ACL rupture were found to be lateral meniscal tears (72.7%), which overwhelmingly outnumbered the frequency of medial meniscal tears in the same group (10.6%) [30]. Bone bruising of the lateral compartment has also been more frequently observed than in the medial compartment in MR images of the knee within 4 wk of ACL rupture [31,32], with posterior-lateral bone bruising demonstrated in nearly 80% of ACL tears observed using MRI [33].…”
Section: Discussionmentioning
confidence: 93%
“…Both orthopedic and radiology literature have reported a significant association between the meniscus tears and ACL injury, and that these ACL injuries are more commonly associated with the lateral meniscus (LM) tears than medial meniscus (MM) tears. 129 Also, associations between BME and meniscal tears have been demonstrated in studies of the acute ACL injuries reporting that these lesions as predominantly located on the lateral side of the joint. 130−132 Nishimori et al, 133 reporting clinical findings based on MRI and arthroscopy in patients with acute ACL injuries, emphasized the importance that needs to be attributed to the cartilage damage of the posterior lateral tibial plateau as well as to the posterior horn tears in the LM.…”
Section: Meniscus In Osteoarthritismentioning
confidence: 97%